Experimental and Numerical Investigation of Annular Casing Impingement Arrays for Faster Casing Response - Dann, A; Dhopade, P; Bacic, M; Ireland, P; Lewis, L (American Society of Mechanical Engineers, 2016)
The Transient Heat Transfer Facility (THTF) was developed at the University of Oxford to test full-scale high pressure compressor and turbine casing air systems using gas turbine engine representative secondary air system mass flow rates, total temperatures and total pressures. Transient casing response together with blade and disc responses governs achievable tip clearances in both compressors and turbines. Traditionally, casing thermal response is faster than disc response and so requires cooling. However, future engine designs may have thermal responses of the discs that are faster than the casings. In this paper we investigate the use of air impingement as a means to speed up the casing response to match such future designs. Two different impingement configurations were selected from a total of eight designs based on steady Reynolds-averaged Navier-Stokes (RANS) predictions of maximum heat transfer coefficient (HTC). The 3D thermal growth of the casing was characterised by the surface temperature rise over a given period of time to assess achievable dynamic response. The configurations were tested in the THTF as a rainbow set. The resulting casing metal temperatures were used in conjunction with an explicit solution of the conduction in the casing wall to calculate HTC due to impingement. The experimental set-up resembles a typical aircraft engine and therefore includes measurement uncertainties arising from features such as fixtures, seals, geometries and large surface areas that are then subjected to varying thermal inertias. These can lead to circumferential temperature non-uniformities, as evident from the experimental results. An uncertainty analysis was performed to quantify these effects on the overall casing thermal response. The experimental data was then compared against numerical predictions from an axisymmetric, 90° sector, conjugate heat transfer model of the facility using the two impingement plate designs. Overall, the values of HTC agreed well across the experimental and numerical results. Both approaches predicted differences in which of the two designs was more effective; however, advantages and limitations were identified in both approaches. The combined experimental and numerical study shows the significance of analysing the full annulus, at engine representative conditions and the benefit of an impingement array to potentially speed up casing response for future engines.